Trajetória da agroindústria canavieira em Alagoas: desindustrialização e os impactos do regime neoliberal desde a década de 1990 - Melo, Érick Silva de (2024)
In a national context characterized by regional disparities, Alagoas faces various problems within its Sugarcane Agroindustrial Complex (CAC), primarily due to neoliberal policies that intensified from the 1990s onward. These policies introduced a new paradigm in the region, negatively impacting the CAC. Trade deregulation, an emphasis on international competitiveness, and the devaluation of the Brazilian real triggered a process of deindustrialization. Amidst these challenges, an agroindustrial sugarcane oligarchy rose to power, concentrating wealth and political influence. This elite, benefitting from neoliberal policies, perpetuated social inequality and labor exploitation, relegating workers to poverty and unemployment. The post-Sugar and Alcohol Institute (IAA) period was marked by a productive restructuring led by large conglomerates. This restructuring, prioritizing ultra-specialization in the sugar-energy sector, deepened imbalances and dependence on monoculture. State interventions in the agroindustrial sector, shaped by neoliberal policies, generated direct impacts on local economic development. Unrestrained environmental exploitation, soil degradation, and water pollution worsened, threatening the sector's sustainability and the population's quality of life. The deindustrialization of the CAC is a phenomenon whose effects transcend local boundaries. Exchange rates, imports, exports, and other economic factors were profoundly affected, leading to various negative consequences. The sugar-alcohol sector is not limited to mere commodity production; however, with the implementation of neoliberal policies, this potential was suppressed, exacerbating poverty and inequality. This research aims to analyze the evolution of the Alagoan sugarcane agroindustrial sector since 1990, diagnosing problems and proposing solutions for a more inclusive and sustainable development. The specific objectives are: (1) to analyze structural changes in the sugarcane agroindustrial sector, (2) to examine inequality indicators and their relations to sector transformations, (3) to investigate the regulation of the agroindustrial sector, (4) to identify the neoliberal policies that affected this regulation, and (5) to analyze the impacts of deindustrialization on regional development. The research focuses on productive diversification, valuing family farming, access to credit and technology for small producers, environmental protection, and promoting fairer and more equitable productive chains. Thus, this work adopted explanatory methodologies to uncover the main problems shaping the CAC in Alagoas. The outcomes of this investigation include promoting agricultural production diversification to reduce dependence on sugarcane monoculture, implementing public policies for sustainable agroindustrial development, combating labor exploitation with improvements in working conditions, stricter environmental protection, and stimulating research and technological innovation. These results aim not only to understand but also to propose practical solutions to the challenges faced by the sector in Alagoas.